Evaluasi Usability dan Penyusunan Rekomendasi Rancangan Antarmuka Pengguna Sistem Informasi Aplikasi Guru Surabaya (SIAGUS) pada SMP Negeri 13 Surabaya - Hasna Rizki Kurnia Annafi; Ismiarta Aknuranda; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
SIAGUS is a teacher platform used to monitor the process of teachers' performances like teachers' promotion, teachers report to get performance allowances, teachers' data, performance appraisal, attendance, licensing or permission. SIAGUS facilitate teacher from Elementary teachers to Junior High School teachers whether they civil servants or not. This research is started by literature review. It is used as sources and references in doing the research. The next steps are choosing the respondents and design evaluation task which contains task scenarios which makes all the information gathered from the respondents is organized well. Next is usability testing evaluation and system usability scale questionnaire (SUS). In this step, data collecting is done by analyzing using ISO 9241-11 effectiveness, efficiency and satisfaction. From the problems found, the researchers compiled an interface design recommendation in the form of prototype based on the guidelines.